To solve the equation \( x^2 - 22x + 1 = 15 \) by completing the square, we will follow these steps:
-
Move the constant term to the other side: \[ x^2 - 22x + 1 - 15 = 0 \implies x^2 - 22x - 14 = 0 \]
-
Complete the square on the left side. We need to take half of the coefficient of \( x \), which is \( -22 \), halve it to get \( -11 \), and then square it to get \( 121 \): \[ x^2 - 22x + 121 - 121 - 14 = 0 \] Simplifying: \[ (x - 11)^2 - 135 = 0 \]
-
Isolate the square: \[ (x - 11)^2 = 135 \]
-
Take the square root of both sides: \[ x - 11 = \pm \sqrt{135} \]
-
Solve for x: \[ x = 11 \pm \sqrt{135} \]
Finally, we break down \( \sqrt{135} \): \[ \sqrt{135} = \sqrt{9 \cdot 15} = 3\sqrt{15} \] So, we have: \[ x = 11 \pm 3\sqrt{15} \]
Thus, the solutions are: \[ x = 11 + 3\sqrt{15}, \quad x = 11 - 3\sqrt{15} \]
The correct response is: x equals 11 plus 3√15, 11 minus 3√15.